Theory Lemmas_S_Finite_Measure_Monad
text ‹For the terminology of s-finite measures/kernels, we refer to the work by Staton~\cite{staton_2017}.
For the definition of the s-finite measure monad, we refer to the lecture note by Yang~\cite{HongseokLecture2017}.
The construction of the s-finite measure monad is based on the detailed pencil-and-paper proof by Tetsuya Sato.
›
section ‹ Lemmas ›
theory Lemmas_S_Finite_Measure_Monad
imports "HOL-Probability.Probability" "Standard_Borel_Spaces.StandardBorel"
begin
lemma integrable_mono_measure:
fixes f :: "'a ⇒ 'b::{banach, second_countable_topology}"
assumes [measurable_cong,measurable]:"sets M = sets N" "M ≤ N" "integrable N f"
shows "integrable M f"
using assms(3) nn_integral_mono_measure[OF assms(1,2),of "λx. ennreal (norm (f x))"]
by(auto simp: integrable_iff_bounded)
lemma AE_mono_measure:
assumes "sets M = sets N" "M ≤ N" "AE x in N. P x"
shows "AE x in M. P x"
by (metis (no_types, lifting) AE_E Collect_cong assms eventually_ae_filter le_measure le_zero_eq null_setsI sets_eq_imp_space_eq)
lemma finite_measure_return:"finite_measure (return M x)"
by(auto intro!: finite_measureI) (metis ennreal_top_neq_one ennreal_zero_neq_top indicator_eq_0_iff indicator_eq_1_iff)
lemma nn_integral_return':
assumes "x ∉ space M"
shows "(∫⇧+ x. g x ∂return M x) = 0"
proof -
have "emeasure (return M x) A = 0" for A
by(cases "A ∈ sets M",insert assms) (auto simp: indicator_def emeasure_notin_sets dest: sets.sets_into_space)
thus ?thesis
by(auto simp: nn_integral_def simple_integral_def) (meson SUP_least le_zero_eq)
qed
lemma pair_measure_return: "return M l ⨂⇩M return N r = return (M ⨂⇩M N) (l,r)"
proof(safe intro!: measure_eqI)
fix A
assume "A ∈ sets (return M l ⨂⇩M return N r)"
then have A[measurable]:"A ∈ sets (M ⨂⇩M N)" by simp
note [measurable_cong] = sets_return[of M] sets_return[of N]
interpret finite_measure "return N r" by(simp add: finite_measure_return)
consider "l ∉ space M" | "r ∉ space N" | "l ∈ space M" "r ∈ space N" by auto
then show "emeasure (return M l ⨂⇩M return N r) A = emeasure (return (M ⨂⇩M N) (l, r)) A" (is "?lhs = ?rhs")
by(cases, insert sets.sets_into_space[OF A]) (auto simp: emeasure_pair_measure nn_integral_return' space_pair_measure nn_integral_return, auto simp: indicator_def)
qed simp_all
lemma null_measure_distr: "distr (null_measure M) N f = null_measure N"
by(auto intro!: measure_eqI simp: distr_def emeasure_sigma)
lemma integral_measurable_subprob_algebra2:
fixes f :: "_ ⇒ _ ⇒ _::{banach,second_countable_topology}"
assumes [measurable]: "(λ(x, y). f x y) ∈ borel_measurable (M ⨂⇩M N)" "L ∈ measurable M (subprob_algebra N)"
shows "(λx. integral⇧L (L x) (f x)) ∈ borel_measurable M"
proof -
note integral_measurable_subprob_algebra[measurable]
note measurable_distr2[measurable]
have "(λx. integral⇧L (distr (L x) (M ⨂⇩M N) (λy. (x, y))) (λ(x, y). f x y)) ∈ borel_measurable M"
by measurable
then show "(λx. integral⇧L (L x) (f x)) ∈ borel_measurable M"
by (rule measurable_cong[THEN iffD1, rotated])
(simp add: integral_distr)
qed
lemma distr_id':
assumes "sets N = sets M"
and "⋀x. x ∈ space N ⟹ f x = x"
shows "distr N M f = N"
by(simp add: distr_cong[OF refl refl,of N f id,simplified,OF assms(2),simplified] distr_id2[OF assms(1)[symmetric]] id_def)
lemma measure_density_times:
assumes [measurable]:"S ∈ sets M" "X ∈ sets M" "r ≠ ∞"
shows "measure (density M (λx. indicator S x * r)) X = enn2real r * measure M (S ∩ X)"
proof -
have [simp]:"density M (λx. indicator S x * r) = density (density M (indicator S)) (λ_. r)"
by(simp add: density_density_eq)
show ?thesis
by(simp add: measure_density_const[OF _ assms(3)] measure_restricted)
qed
lemma complete_the_square:
fixes a b c x :: real
assumes "a ≠ 0"
shows "a*x⇧2 + b * x + c = a * (x + (b / (2*a)))⇧2 - ((b⇧2 - 4* a * c)/(4*a))"
using assms by(simp add: comm_semiring_1_class.power2_sum power2_eq_square[of "b / (2 * a)"] ring_class.ring_distribs(1) division_ring_class.diff_divide_distrib power2_eq_square[of b])
lemma complete_the_square2':
fixes a b c x :: real
assumes "a ≠ 0"
shows "a*x⇧2 - 2 * b * x + c = a * (x - (b / a))⇧2 - ((b⇧2 - a*c)/a)"
using complete_the_square[OF assms,where b="-2 * b" and x=x and c=c]
by(simp add: division_ring_class.diff_divide_distrib assms)
lemma normal_density_mu_x_swap:
"normal_density μ σ x = normal_density x σ μ"
by(simp add: normal_density_def power2_commute)
lemma normal_density_plus_shift: "normal_density μ σ (x + y) = normal_density (μ - x) σ y"
by(simp add: normal_density_def add.commute diff_diff_eq2)
lemma normal_density_times:
assumes "σ > 0" "σ' > 0"
shows "normal_density μ σ x * normal_density μ' σ' x = (1 / sqrt (2 * pi * (σ⇧2 + σ'⇧2))) * exp (- (μ - μ')⇧2 / (2 * (σ⇧2 + σ'⇧2))) * normal_density ((μ*σ'⇧2 + μ'*σ⇧2)/(σ⇧2 + σ'⇧2)) (σ * σ' / sqrt (σ⇧2 + σ'⇧2)) x"
(is "?lhs = ?rhs")
proof -
have non0: "2*σ⇧2 ≠ 0" "2*σ'⇧2 ≠ 0" "σ⇧2 + σ'⇧2 ≠ 0"
using assms by auto
have "?lhs = exp (- ((x - μ)⇧2 / (2 * σ⇧2))) * exp (- ((x - μ')⇧2 / (2 * σ'⇧2))) / (sqrt (2 * pi * σ⇧2) * sqrt (2 * pi * σ'⇧2)) "
by(simp add: normal_density_def)
also have "... = exp (- ((x - μ)⇧2 / (2 * σ⇧2)) - ((x - μ')⇧2 / (2 * σ'⇧2))) / (sqrt (2 * pi * σ⇧2) * sqrt (2 * pi * σ'⇧2))"
by(simp add: exp_add[of "- ((x - μ)⇧2 / (2 * σ⇧2))" "- ((x - μ')⇧2 / (2 * σ'⇧2))",simplified add_uminus_conv_diff])
also have "... = exp (- (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2 / (2 * (σ * σ' / sqrt (σ⇧2 + σ'⇧2))⇧2) - (μ - μ')⇧2 / (2 * (σ⇧2 + σ'⇧2))) / (sqrt (2 * pi * σ⇧2) * sqrt (2 * pi * σ'⇧2))"
proof -
have "((x - μ)⇧2 / (2 * σ⇧2)) + ((x - μ')⇧2 / (2 * σ'⇧2)) = (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2 / (2 * (σ * σ' / sqrt (σ⇧2 + σ'⇧2))⇧2) + (μ - μ')⇧2 / (2 * (σ⇧2 + σ'⇧2))"
(is "?lhs' = ?rhs'")
proof -
have "?lhs' = (2 * ((x - μ)⇧2 * σ'⇧2) + 2 * ((x - μ')⇧2 * σ⇧2)) / (4 * (σ⇧2 * σ'⇧2))"
by(simp add: field_class.add_frac_eq[OF non0(1,2)])
also have "... = ((x - μ)⇧2 * σ'⇧2 + (x - μ')⇧2 * σ⇧2) / (2 * (σ⇧2 * σ'⇧2))"
by(simp add: power2_eq_square division_ring_class.add_divide_distrib)
also have "... = ((σ⇧2 + σ'⇧2) * x⇧2 - 2 * (μ * σ'⇧2 + μ' * σ⇧2) * x + (μ'⇧2 * σ⇧2 + μ⇧2 * σ'⇧2)) / (2 * (σ⇧2 * σ'⇧2))"
by(simp add: comm_ring_1_class.power2_diff ring_class.left_diff_distrib semiring_class.distrib_right)
also have "... = ((σ⇧2 + σ'⇧2) * (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2 - ((μ * σ'⇧2 + μ' * σ⇧2)⇧2 - (σ⇧2 + σ'⇧2) * (μ'⇧2 * σ⇧2 + μ⇧2 * σ'⇧2)) / (σ⇧2 + σ'⇧2)) / (2 * (σ⇧2 * σ'⇧2))"
by(simp only: complete_the_square2'[OF non0(3),of x "(μ * σ'⇧2 + μ' * σ⇧2)" "(μ'⇧2 * σ⇧2 + μ⇧2 * σ'⇧2)"])
also have "... = ((σ⇧2 + σ'⇧2) * (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2) / (2 * (σ⇧2 * σ'⇧2)) - (((μ * σ'⇧2 + μ' * σ⇧2)⇧2 - (σ⇧2 + σ'⇧2) * (μ'⇧2 * σ⇧2 + μ⇧2 * σ'⇧2)) / (σ⇧2 + σ'⇧2)) / (2 * (σ⇧2 * σ'⇧2))"
by(simp add: division_ring_class.diff_divide_distrib)
also have "... = (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2 / (2 * ((σ * σ') / sqrt (σ⇧2 + σ'⇧2))⇧2) - (((μ * σ'⇧2 + μ' * σ⇧2)⇧2 - (σ⇧2 + σ'⇧2) * (μ'⇧2 * σ⇧2 + μ⇧2 * σ'⇧2)) / (σ⇧2 + σ'⇧2)) / (2 * (σ⇧2 * σ'⇧2))"
by(simp add: monoid_mult_class.power2_eq_square[of "(σ * σ') / sqrt (σ⇧2 + σ'⇧2)"] ab_semigroup_mult_class.mult.commute[of "σ⇧2 + σ'⇧2"] )
(simp add: monoid_mult_class.power2_eq_square[of σ] monoid_mult_class.power2_eq_square[of σ'])
also have "... = (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2 / (2 * (σ * σ' / sqrt (σ⇧2 + σ'⇧2))⇧2) - ((μ * σ'⇧2)⇧2 + (μ' * σ⇧2)⇧2 + 2 * (μ * σ'⇧2) * (μ' * σ⇧2) - (σ⇧2 * (μ'⇧2 * σ⇧2) + σ⇧2 * (μ⇧2 * σ'⇧2) + (σ'⇧2 * (μ'⇧2 * σ⇧2) + σ'⇧2 * (μ⇧2 * σ'⇧2)))) / ((σ⇧2 + σ'⇧2) * (2 * (σ⇧2 * σ'⇧2)))"
by(simp add: comm_semiring_1_class.power2_sum[of "μ * σ'⇧2" "μ' * σ⇧2"] semiring_class.distrib_right[of "σ⇧2" "σ'⇧2" "μ'⇧2 * σ⇧2 + μ⇧2 * σ'⇧2"] )
(simp add: semiring_class.distrib_left[of _ "μ'⇧2 * σ⇧2 " "μ⇧2 * σ'⇧2"])
also have "... = (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2 / (2 * (σ * σ' / sqrt (σ⇧2 + σ'⇧2))⇧2) + ((σ⇧2 * σ'⇧2)*μ⇧2 + (σ⇧2 * σ'⇧2)*μ'⇧2 - (σ⇧2 * σ'⇧2) * 2 * (μ*μ')) / ((σ⇧2 + σ'⇧2) * (2 * (σ⇧2 * σ'⇧2)))"
by(simp add: monoid_mult_class.power2_eq_square division_ring_class.minus_divide_left)
also have "... = (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2 / (2 * (σ * σ' / sqrt (σ⇧2 + σ'⇧2))⇧2) + (μ⇧2 + μ'⇧2 - 2 * (μ*μ')) / ((σ⇧2 + σ'⇧2) * 2)"
using assms by(simp add: division_ring_class.add_divide_distrib division_ring_class.diff_divide_distrib)
also have "... = ?rhs'"
by(simp add: comm_ring_1_class.power2_diff ab_semigroup_mult_class.mult.commute[of 2])
finally show ?thesis .
qed
thus ?thesis
by simp
qed
also have "... = (exp (- (μ - μ')⇧2 / (2 * (σ⇧2 + σ'⇧2))) / (sqrt (2 * pi * σ⇧2) * sqrt (2 * pi * σ'⇧2))) * sqrt (2 * pi * (σ * σ' / sqrt (σ⇧2 + σ'⇧2))⇧2) * normal_density ((μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2)) (σ * σ' / sqrt (σ⇧2 + σ'⇧2)) x"
by(simp add: exp_add[of "- (x - (μ * σ'⇧2 + μ' * σ⇧2) / (σ⇧2 + σ'⇧2))⇧2 / (2 * (σ * σ' / sqrt (σ⇧2 + σ'⇧2))⇧2)" "- (μ - μ')⇧2 / (2 * (σ⇧2 + σ'⇧2))",simplified] normal_density_def)
also have "... = ?rhs"
proof -
have "exp (- (μ - μ')⇧2 / (2 * (σ⇧2 + σ'⇧2))) / (sqrt (2 * pi * σ⇧2) * sqrt (2 * pi * σ'⇧2)) * sqrt (2 * pi * (σ * σ' / sqrt (σ⇧2 + σ'⇧2))⇧2) = 1 / sqrt (2 * pi * (σ⇧2 + σ'⇧2)) * exp (- (μ - μ')⇧2 / (2 * (σ⇧2 + σ'⇧2)))"
using assms by(simp add: real_sqrt_mult)
thus ?thesis
by simp
qed
finally show ?thesis .
qed
lemma KL_normal_density:
assumes [arith]: "b > 0" "d > 0"
shows "KL_divergence (exp 1) (density lborel (normal_density a b)) (density lborel (normal_density c d)) = ln (b / d) + (d⇧2 + (c - a)⇧2) / (2 * b⇧2) - 1 / 2" (is "?lhs = ?rhs")
proof -
have "?lhs = (∫x. normal_density c d x * ln (normal_density c d x / normal_density a b x) ∂lborel)"
by(unfold log_ln,rule lborel.KL_density_density) (use order.strict_implies_not_eq[OF normal_density_pos[of b a]] in auto)
also have "... = (∫x. normal_density c d x * ln (normal_density c d x) - normal_density c d x * ln (normal_density a b x) ∂lborel)"
by(simp add: ln_div[OF normal_density_pos[OF assms(2)] normal_density_pos[OF assms(1)]] right_diff_distrib)
also have "... = (∫x. normal_density c d x * ln (exp (- (x - c)⇧2 / (2 * d⇧2)) / sqrt (2 * pi * d⇧2)) - normal_density c d x * ln (exp (- (x - a)⇧2 / (2 * b⇧2)) / sqrt (2 * pi * b⇧2)) ∂lborel)"
by(simp add: normal_density_def)
also have "... = (∫x. normal_density c d x * (- (x - c)⇧2 / (2 * d⇧2) - ln (sqrt (2 * pi * d⇧2))) - (normal_density c d x * (- (x - a)⇧2 / (2 * b⇧2) - ln (sqrt (2 * pi * b⇧2)))) ∂lborel)"
by(simp add: ln_div)
also have "... = (∫x. normal_density c d x * (ln (sqrt (2 * pi * b⇧2)) - ln (sqrt (2 * pi * d⇧2))) + (normal_density c d x * ((x - a)⇧2 / (2 * b⇧2)) - normal_density c d x * ((x - c)⇧2 / (2 * d⇧2))) ∂lborel)"
by(auto intro!: Bochner_Integration.integral_cong simp: right_diff_distrib)
also have "... = (∫x. normal_density c d x * (ln (sqrt (2 * pi * b⇧2)) - ln (sqrt (2 * pi * d⇧2))) + (normal_density c d x * ((x - c)⇧2 / (2 * b⇧2) + (2 * x * (c - a) + a^2 - c^2) / (2 * b⇧2)) - normal_density c d x * ((x - c)⇧2 / (2 * d⇧2))) ∂lborel)"
by(auto intro!: Bochner_Integration.integral_cong simp: add_divide_distrib[symmetric] power2_diff) (simp add: right_diff_distrib)
also have "... = (∫x. (ln (sqrt (2 * pi * b⇧2)) - ln (sqrt (2 * pi * d⇧2))) * normal_density c d x + ((1 / (2 * b⇧2) * (normal_density c d x * (x - c)⇧2) + (2 * (c - a)) / (2 * b⇧2) * (normal_density c d x * x) + (a^2 - c^2) / (2 * b⇧2) * (normal_density c d x)) - 1 / (2 * d⇧2) * (normal_density c d x * (x - c)⇧2)) ∂lborel)"
by(auto intro!: Bochner_Integration.integral_cong simp: add_divide_distrib[symmetric] ring_distribs)
also have "... = (∫x. (ln (sqrt (2 * pi * b⇧2)) - ln (sqrt (2 * pi * d⇧2))) * normal_density c d x ∂lborel) + (((∫x. 1 / (2 * b⇧2) * (normal_density c d x * (x - c)⇧2) ∂lborel) + (∫x. (2 * (c - a)) / (2 * b⇧2) * (normal_density c d x * x) ∂lborel) + (∫x. (a^2 - c^2) / (2 * b⇧2) * (normal_density c d x) ∂lborel)) - (∫x. 1 / (2 * d⇧2) * (normal_density c d x * (x - c)⇧2) ∂lborel))"
using integrable_normal_moment_nz_1[OF assms(2)] integrable_normal_moment[OF assms(2),where k=2] by simp
also have "... = ln (sqrt (2 * pi * b⇧2)) - ln (sqrt (2 * pi * d⇧2)) + 1 / (2 * b⇧2) * d⇧2 + (2 * c - 2 * a) / (2 * b⇧2) * c + (a⇧2 - c⇧2) / (2 * b⇧2) - 1 / (2 * d⇧2) * d⇧2"
by(simp add: integral_normal_moment_even[OF assms(2),of _ 1,simplified] integral_normal_moment_nz_1[OF assms(2)] del: times_divide_eq_left)
also have "... = ln (b / d) + 1 / (2 * b⇧2) * d⇧2 + (2 * c - 2 * a) / (2 * b⇧2) * c + (a⇧2 - c⇧2) / (2 * b⇧2) - 1 / (2 * d⇧2) * d⇧2"
by(simp add: ln_sqrt ln_mult power2_eq_square diff_divide_distrib[symmetric] ln_div)
also have "... = ?rhs"
by(auto simp: add_divide_distrib[symmetric] power2_diff left_diff_distrib) (simp add: power2_eq_square)
finally show ?thesis .
qed
lemma count_space_prod:"count_space (UNIV :: ('a :: countable) set) ⨂⇩M count_space (UNIV :: ('b :: countable) set) = count_space UNIV"
by(auto simp: pair_measure_countable)
lemma measure_pair_pmf:
fixes p :: "('a :: countable) pmf" and q :: "('b :: countable) pmf"
shows "measure_pmf p ⨂⇩M measure_pmf q = measure_pmf (pair_pmf p q)" (is "?lhs = ?rhs")
proof -
interpret pair_prob_space "measure_pmf p" "measure_pmf q"
by standard
have "?lhs = measure_pmf p ⤜ (λx. measure_pmf q ⤜ (λy. return (measure_pmf p ⨂⇩M measure_pmf q) (x, y)))"
by(rule pair_measure_eq_bind)
also have "... = ?rhs"
by(simp add: measure_pmf_bind pair_pmf_def return_pmf.rep_eq cong: return_cong[OF sets_pair_measure_cong[OF sets_measure_pmf_count_space[of p] sets_measure_pmf_count_space[of q],simplified count_space_prod]])
finally show ?thesis .
qed
lemma distr_PiM_distr:
assumes "finite I" "⋀i. i ∈ I ⟹ sigma_finite_measure (distr (M i) (N i) (f i))"
and "⋀i. i ∈ I ⟹ f i ∈ M i →⇩M N i"
shows "distr (Π⇩M i∈I. M i) (Π⇩M i∈I. N i) (λxi. λi∈I. f i (xi i)) = (Π⇩M i∈I. distr (M i) (N i) (f i))"
proof -
define M' where "M' ≡ (λi. if i ∈ I then M i else null_measure (M i))"
have f[measurable]: "⋀i. i ∈ I ⟹ f i ∈ M' i →⇩M N i" and [measurable_cong]: "⋀i. sets (M' i) = sets (M i)" and [simp]: "⋀i. i ∈ I ⟹ M' i = M i"
by(auto simp: M'_def assms)
interpret product_sigma_finite "λi. distr (M' i) (N i) (f i)"
by(auto simp: product_sigma_finite_def M'_def assms(2)) (auto intro!: finite_measure.sigma_finite_measure finite_measureI simp: null_measure_distr)
interpret ps: product_sigma_finite M'
by(auto simp: product_sigma_finite_def M'_def intro!: finite_measure.sigma_finite_measure[of "null_measure _"] finite_measureI sigma_finite_measure_distr[OF assms(2)])
have "distr (Π⇩M i∈I. M i) (Π⇩M i∈I. N i) (λxi. λi∈I. f i (xi i)) = distr (Π⇩M i∈I. M' i) (Π⇩M i∈I. N i) (λxi. λi∈I. f i (xi i))"
by(simp cong: PiM_cong)
also have "... = (Π⇩M i∈I. distr (M' i) (N i) (f i))"
proof(rule PiM_eqI[OF assms(1)])
fix A
assume "⋀i. i ∈ I ⟹ A i ∈ sets (distr (M' i) (N i) (f i))"
hence h[measurable]:"⋀i. i ∈ I ⟹ A i ∈ sets (N i)"
by simp
have [simp]:"(λxi. λi∈I. f i (xi i)) -` (Pi⇩E I A) ∩ space (Pi⇩M I M') = (Π⇩E i∈I. f i -` A i ∩ space (M' i))"
by(auto simp: space_PiM)
show "emeasure (distr (Pi⇩M I M') (Pi⇩M I N) (λxi. λi∈I. f i (xi i))) (Pi⇩E I A) = (∏i∈I. emeasure (distr (M' i) (N i) (f i)) (A i))"
by(auto simp: emeasure_distr assms(1) ps.emeasure_PiM[OF assms(1)])
qed(simp_all cong: sets_PiM_cong)
also have "... = (Π⇩M i∈I. distr (M i) (N i) (f i))"
by(auto cong: PiM_cong)
finally show ?thesis .
qed
lemma distr_PiM_distr_prob:
assumes "⋀i. i ∈ I ⟹ prob_space (M i)"
and "⋀i. i ∈ I ⟹ f i ∈ M i →⇩M N i"
shows "distr (Π⇩M i∈I. M i) (Π⇩M i∈I. N i) (λxi. λi∈I. f i (xi i)) = (Π⇩M i∈I. distr (M i) (N i) (f i))"
proof -
define M' where "M' ≡ (λi. if i ∈ I then M i else return (count_space UNIV) undefined)"
define N' where "N' ≡ (λi. if i ∈ I then N i else return (count_space UNIV) undefined)"
interpret p: product_prob_space "λi. distr (M' i) (N' i) (f i)"
by(auto simp: product_prob_space_def product_prob_space_axioms_def product_sigma_finite_def M'_def prob_space_return N'_def assms intro!: prob_space_imp_sigma_finite prob_space.prob_space_distr)
interpret p': product_prob_space M'
by(auto simp: product_prob_space_def product_prob_space_axioms_def product_sigma_finite_def M'_def prob_space_return assms intro!: prob_space_imp_sigma_finite)
have f[measurable]: "⋀i. i ∈ I ⟹ f i ∈ M' i →⇩M N' i"
by(auto simp: assms M'_def N'_def)
have [simp]: "p.emb I = prod_emb I N'"
by standard (auto simp: prod_emb_def)
have "distr (Π⇩M i∈I. M i) (Π⇩M i∈I. N i) (λxi. λi∈I. f i (xi i)) = distr (Π⇩M i∈I. M' i) (Π⇩M i∈I. N' i) (λxi. λi∈I. f i (xi i))"
by(simp add: M'_def N'_def cong: PiM_cong)
also have "... = (Π⇩M i∈I. distr (M' i) (N' i) (f i))"
proof(rule p.PiM_eq)
fix J F
assume h[measurable]: "finite J" "J ⊆ I" "⋀j. j ∈ J ⟹ F j ∈ p.M.events j"
then have [measurable]: "⋀j. j ∈ J ⟹ F j ∈ sets (N' j)" by simp
show " emeasure (distr (Pi⇩M I M') (Pi⇩M I N') (λxi. λi∈I. f i (xi i))) (p.emb I J (Pi⇩E J F)) = (∏j∈J. emeasure (distr (M' j) (N' j) (f j)) (F j))" (is "?lhs = ?rhs")
proof -
have "?lhs = emeasure (Pi⇩M I M') ((λxi. λi∈I. f i (xi i)) -` (prod_emb I N' J (Pi⇩E J F)) ∩ space (Pi⇩M I M'))"
by(simp add: emeasure_distr h)
also have "... = emeasure (Pi⇩M I M') (prod_emb I M' J (Π⇩E i∈J. f i -` (F i) ∩ space (M' i)))"
proof -
have [simp]:"(λxi. λi∈I. f i (xi i)) -` (prod_emb I N' J (Pi⇩E J F)) ∩ space (Pi⇩M I M') = prod_emb I M' J (Π⇩E i∈J. f i -` (F i) ∩ space (M' i))"
using measurable_space[OF f] h(1,2,3)
by(fastforce simp: space_PiM prod_emb_def PiE_def extensional_def Pi_def M'_def N'_def)
show ?thesis by simp
qed
also have "... = (∏i∈J. emeasure (M' i) (f i -` (F i) ∩ space (M' i)))"
by(rule p'.emeasure_PiM_emb,insert h(2)) (auto simp: h(1))
also have "... = ?rhs"
using h(2) by(auto simp: emeasure_distr intro!: comm_monoid_mult_class.prod.cong)
finally show ?thesis .
qed
qed (simp cong: sets_PiM_cong)
also have "... = (Π⇩M i∈I. distr (M i) (N i) (f i))"
by(simp add: M'_def N'_def cong: distr_cong PiM_cong)
finally show ?thesis .
qed
end